Time variation paths of risk sensitivities of bank stocks in the past two decades. Issue 4 (15th August 2016) - Chen, Kaiyi; He, Ling T.; Lenin, R.B.
Abstract : Purpose: The purpose of this study is to trace time variation paths in risk sensitivities of bank stock returns over the period of 1990-2014, which covers one of most serious financial crises in the history of the USA. Design/methodology/approach: This study programs the flexible least squares (FLS) approach (Kalaba and Testfatsion, 1988, 1989 and 1990) with R, a free statistical computing and graphics software, to estimate the three-factor model developed by He and Reichert (2003) to examine changes in risk sensitivities of bank stocks to the stock market, bond market and real estate market. Findings: Both FLS and ordinary least squares (OLS) results indicate that the bond market (interest rate) sensitivity of bank stock returns experiences dramatic changes. It is significantly positive before the 2006 subprime mortgage crisis (11/1990 to 5/2006), reduces to insignificant in a short period of 11/2006 to 10/2008 and turns into significantly negative during the period of 11/2008-11/2014. Further, results of this study indicate that bank stocks negatively respond to changes in housing prices in the period of 11/1990-1/1994 and after that the sensitivity turns into significantly positive. The significant shifts in risk sensitivities of banks stock returns coincide with alterations in long-term interest rates and monetary policy, especially the enormously stimulative monetary policy after the financial crisis in 2008. Originality/value: This study programs the FLS approach with R and uses the FLS approach to demonstrate the time variation paths of risk sensitivities of bank stocks over a period that covers the 2008 financial crisis. The OLS results verify the significant shifts in risk sensitivities suggested by the FLS estimates.